Ritual Murder and the Subjectivity of Christ: A Choice in Medieval Christianity - Ocker, Christopher (Harvard theological review, 1998)
This is a study of the emotional context of certain medieval anti-Jewish legends. It examines how the stories redefined the composition of society, the relation of this to popular devotion, and the paradox between a religious intention and its effect. After a brief survey of the phenomenon, I suggest that recent views of the psychological sources of the legends do not adequately account for the religious experience that they promote, nor do these explanations sufficiently account for the way the legends encouraged and reinforced social habits—“ruts in the pathways of the mind” that encouraged the maintenance of conformity among members of society. Part one will examine how the libels could help people imagine more specifically the general hostility against Jews widely propagated after the First Crusade and how this superimposed a social uniformity on the town. Part two describes the emotional context of that violence in devotion to the passion of Christ. Part three considers the moral dilemma posed by the function of these legends in popular devotion. My goal is to account for the religious content of anti-Jewish legend and an ethical problem within medieval piety, for which reason it will be necessary to draw on the diverse literature that shaped medieval Christian culture, both learned and popular, from the twelfth century, when the legends first appeared in Europe, to the eve of the Reformation.